Stem cells as a new option in the treatment of female infertility - Niknazar, Somayeh; Zali, Alireza; Rahmati Roodsari, Sara (Researcher Bulletin of Medical Sciences, 2024)
Infertility is characterized by the failure to attain a successful pregnancy after one year of normal intercourse. Infertility has a negative impact on the mental and psychosocial well-being of influenced couples, result to reduced quality of life. Infertility is recognized as a global health problem, plague nearly 15% of couples worldwide. It can result from female-related factors (30%), such as premature ovarian failure and uterine disease [1]. Despite recent advances in assisted reproductive technology (ART), many couples are incapable to conceive except through gamete and embryo donation or adoption [2]. Cell-based therapy for fertility restoration is an active research field in some countries. Stem cells are primitive cells found in almost all tissues. They are unspecialized cells with the ability to differentiate, self-renew and proliferate. The mechanism of stem cell function in infertility treatment is to replace injured cells and restore the structure and function of affected organs [3]. Stem cells show renewed hope in overcoming problems associated with infertility in several preclinical and clinical studies [4]. For women infertility, stem cells may be applied to regenerate ovaries, oocyte and/or endometrium [5, 6]. This field started with a provocative publication in 2004. In this publication, endometrial biopsies from a small number of women who underwent bone marrow transplantation were examined and found donor-derived cells levels is nearly half of the epithelial and stromal cells in the biopsy samples [7]. Dr. Verter reviewed 5695 advanced cell therapy clinical trials from 2011 to 2020 from the CellTrials.org database and extracted 112 of this trials specifically targeting medical diagnoses that affect fertility [8]. Clinical research report that stem cells can be used to increase the thickness of the uterus [9]. Stem cell-derived gametes can now be used as an in vitro model for evaluating drug effects [10]. Overall, stem cell research has provided new breakthroughs in fertility treatment [4]. Clinical use of stem cells must be consistent with ethical requirements, such as free and informed consent and other ethical principles of clinical research. Endometrial cell therapy may be cheaper and more accessible than surrogacy if it can progress from clinical trials to an approved treatment available to the public [11]. However, increasingly large-scale clinical trials are needed to demonstrate the safety and efficacy of stem cell therapy in the human reproduction field.